The Effect of Online Game Addiction on the Quality of Student Education During the COVID-19 Pandemic - Bernadetha Nadeak (Jurnal Pendidikan dan Pengajaran, 2021)
The ongoing COVID-19 pandemic has had a severe impact on the quality of education in Indonesia. This causes many students to become addicted to online games which will have an impact on children's knowledge, skills, and attitudes. This study aims to describe addiction's effect on the quality of student education during the COVID-19 pandemic in Indonesia. This research is a literature study with a qualitative approach. The results show that during the COVID-19 outbreak, game data usage is reported to have increased worldwide, and download volume games have reached highs record in Asia, including Indonesia. This is caused by games used to cope with the psychological stress caused by the outbreak. Traditional games that were once popular have been replaced by new games such as online video games. Stakeholders should be aware of how addiction increases to online games, especially during a pandemic, and can contribute to the risk of disruption to the quality of student learning, especially if the pandemic continues. The government must formulate alternative ways to avoid online game addiction during the COVID-19 pandemic for people, especially teenagers, which can interfere with the quality of their education.